Hans Jacob Nilsens og Stein Bugges teatersyn: To retninger i re-teatraliseringen av 1930- og 40-årenes teater i Norge - Leirvåg, Siren (Teatervitenskapelige studier, 2023)
The 1930s and -40s can be described as a period of change and revolt in Norwegian theatre. In this article I will highlight the work and ideology of two of our significant contributors to the contemporary and the future theatre of their time: Hans Jacob Nilsen (1897–1957) and Stein Bugge (1896–1961). Particularly interesting are their artistic and ideological program for a theatre more in sync with the political and cultural movements of their time. Nilsen and Bugge functioned as artistic directors of Den Nationale Scene (DNS) in Bergen in each decade (1934-39 and 1947-48). Both leaned heavily on the theatre development of Central and Eastern Europe and what we can call the re-theatricalization of European theatre. That means a closer focus on the means of theatre production and the potential effect on society in context. The main question is: In what direction did Nilsen and Bugge intend to pull Norwegian Theatre artistically and in terms of cultural policy?